LAS TOXINAS Y EL VENENO DEL ALACRAN - ANGUIANO, LG (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1947)
Inhibitory effects on the contraction of the cat's nictitating membrane are produced, (a) by stimulation of the central end of vagus nerve, and (b) after distention of the aorta, by increase of its internal blood pressure These effects are obtainable aft
BOL INST ESTUD MED BIOL
Keywords: TOXINAS, VENENO, ALACRAN; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA CLINICA